The Study Program Selection System: Integrated Analytical Hierarchy Process (AHP) and Technique For Others Preference by Similarity to Ideal Solution (TOPSIS) Approach - Erlina, Marni; Okfalisa, Okfalisa (IT journal research and development (Online), 2023)
The study program selection in several high schools or madrasah aliyah (MA) in Riau province is conducted manually. The initial survey found that the study program is commonly chosen by following the friend’s preference and parents’ option instead of their knowledge capability and desire. As a reflection, many students fail to adhere to the school subjects, obtain unsatisfactory results, and even change their study program. Therefore, this paper aims to assist students in altering the appropriate study program by considering students' capabilities, talents and interests by developing a multi-criteria decision support system (DSS). This DSS employs the integrated AHP approach for criteria weighting and TOPSIS for ranking alternatives.  Herein, seventy students' data from grade ten MAN 2 Kuantan Singingi grows into this case study. The automation system analysis is executed through the web base DSS system using PHP programming language and MySQL database. As a result, AHP calculates the significance values of the criterion whereby the student interest score values at 0.34, academic report, potential academic test, physiological test, Pre-Test/Post-Test, interview scores, and teacher recommendation scores at 0.21, 0.14, 0.11, 0.09, 0.06, and 0.05, respectively. Subsequently, TOPSIS ranks the students according to the assessment and criteria weighting based on the standard requirement of study program in Mathematics and Science program (MIPA) and Social Science program (IIS). The DSS study program selection application has been tested using the Blackbox and User Acceptance Test (UAT) methods. Both of these approaches indicate that this application is functionally approved and capable of aiding the users in the optimal study program selection, with 81.9% agreement. In a nutshell, this DSS has successfully recommended the optimum study program per the students’ talents, interests, and capabilities and provided the direction development of students’ expertise area for the next level of education.